(untitled) (Margalla Papers, 2021)
Media, as a source of information, plays a crucial role in opinion-making and perception-building. During the Iraq War (2003), the media's role was to shape the images of war while propagating specific ideas to influence the people. As a result, the world perceived propagandistic messages that appeared to take the form of fake news. The disinformation campaign was designed to profess the threat of weapons of mass destruction and explicate Saddam Hussein's affiliation with terrorist organizations as a threat to the world. The instantly shared live images, videos, recordings, and pictures across mass media platforms elicited shock, dismay, and disbelief throughout the world. With this insight, this paper attempts to comprehend the role of media propaganda which promoted the agenda of a media spectacle of the US military victory by transforming into a presentation of anarchy that destabilizes the rationale behind the invasion. It also provides an overview of the development of the Iraq War through the lens of the Herman-Chomsky Propaganda model. This model elucidates the role of propaganda in manipulating the opinion of the Iraqi people and how it was used to achieve economic, social, and political advantages. Bibliography Entry Javed, Huma, and Arshi Saleem Hashmi. 2021. “Corporate Media Manipulation in the US Wars: A Case Study of Iraq War.” Magalla Papers 25 (1): 143-152.